Which factor affects the storage of real-world object information in visual working memory: perceptual or conceptual information? - Li, Qiankai; Chen, Zhen; Sun, Qi; Li, Xinyu (Frontiers in Psychology, 2023)
Visual working memory (VWM) is a limited dynamic memory system where people temporarily store and process visual information (Baddeley & Hitch, 1974;Cowan, 2008). Previous research showed that real-world objects do not have a fixed capacity compared to simple ones (Brady et al., 2016). Konkle et al. (2010) found that the conceptual information and perception information of real-world objects had different effects on visual long-term memory (VLTM) capacity. VLTM capacity was more dependent on conceptual information than the perceptual distinctiveness of real-world objects. However, we did not know how the intrinsic attribute of real-world objects affects VWM capacity yet. In the current research, we set five experiments to explore the comparative effects of conceptual versus perceptual information of real-world objects in VWM capacity. Our results suggested that VWM capacity was more dependent on the perceptual distinctiveness of real-world objects than on conceptual structure. These data provide evidence that VWM capacity for real-world objects depends more on perceptual information than on conceptual structure.